The Role of Indonesian National Armed Forces in the Civil Conflict in Maluku - Fatgehipon, Abdul Haris (KnE Social Sciences, 2024)
The civil conflict that occurred in Ambon caused the Indonesian government to send the Indonesian National Armed Forces to assist the police in securing Ambon. The involvement of the military and security guards in the Ambon area proved helpful in providing a sense of security, even though many people criticize the involvement of the Indonesian National Armed Forces in securing the conflict in Ambon. The study methodology is descriptive qualitative. Researchers conducted field research in Ambon. through interviews with the community, religious leaders, community leaders, and military leaders. The author has also conducted archival research. The results of the study show that the Indonesian National Armed Forces played an important role in assisting in securing the Ambon conflict. Although the Ambon conflict has ended, the Indonesian National Armed Forces is still assigned to assist the police in security. Keywords: military, civil conflict, Maluku